2022
DOI: 10.1002/jpln.202100357
|View full text |Cite
|
Sign up to set email alerts
|

Lime requirement for agricultural soils: A review of the current and potential methods for routine use

Abstract: Liming is one of the key agronomic practices to improve crop yields in acid soils because, among other things, it reduces aluminum toxicity and creates favorable conditions for crop growth. For an effective liming program, the methods to determine lime requirement should be as precise as possible. This paper reviews the existing lime requirement methods and discusses the potential of a new one suitable for routine use in the laboratory to test most agricultural soils. The most widely used lime requirement meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
(180 reference statements)
0
4
0
Order By: Relevance
“…Availability of phosphorous might be as a result of applying biochar and lime that reducing the activity of toxic ions, e.g., Fe and Al in soil reactions. Biochar can increase soil P sorption and help to increase the supply of mineralized phosphorous [36] and lime infuences the soluble Al, H, and Fe to nontoxic levels and indirectly increases microbial activity to promote the use of remaining nutrients by plants [22]. Te positive correlation between accessible p and pH (0.62%) showed that soil pH has a signifcant role in controlling the amount of P that is available to plants.…”
Section: Soil Available Phosphorousmentioning
confidence: 99%
See 1 more Smart Citation
“…Availability of phosphorous might be as a result of applying biochar and lime that reducing the activity of toxic ions, e.g., Fe and Al in soil reactions. Biochar can increase soil P sorption and help to increase the supply of mineralized phosphorous [36] and lime infuences the soluble Al, H, and Fe to nontoxic levels and indirectly increases microbial activity to promote the use of remaining nutrients by plants [22]. Te positive correlation between accessible p and pH (0.62%) showed that soil pH has a signifcant role in controlling the amount of P that is available to plants.…”
Section: Soil Available Phosphorousmentioning
confidence: 99%
“…In addition, lime enhances soil physical qualities and can be used for more than three years [7,[18][19][20]. In general, lime is valuable, but it has some drawbacks, including high transport costs, potential restrictions on practical applications, and negative efects on trace element shortages [21,22]. Additionally, in the western region of Ethiopia, there is a gap in the lime recommendations based on the particular crop kinds and soil conditions [18].…”
Section: Introductionmentioning
confidence: 99%
“…Various methods for determining LR have been developed including soil–buffer methods, titrations, incubations and equations based on soil characteristics (Nguyen, 2022). Most commonly, estimates for LR are derived through the utilization of buffer methods, owing to their ease of use, swift analysis and cost‐effectiveness (McFarland et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…An equation can be applied to a 30‐min measurement to estimate a longer buffering reaction and a predictive equation was created by UGA calibrated from US soils (Kissel et al., 2012; Sikora & Moore, 2012; Thompson et al., 2010). This method is a promising alternative method for routine lab use with some further evaluation required (Nguyen, 2023). Established charts (FAS, 2019) and proven models (Rothamsted Research, 2022) are widely adopted for rapid value estimates.…”
Section: Introductionmentioning
confidence: 99%